PESAN DAKWAH MELALUI MEDIA MASSA: STUDI PENDEKATAN TELEVISI SEBAGAI DA’I - A.Rafik (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2019)
This research describes how da'wah messages through television or electronic media. The development of dakwah in this modern era, has enabled clerics and clerics to convey da'wah messages not only using the talaqqi (face-to-face) method, but also using various kinds of media, both printed and electronic, audio, visual and audio-visual. The use of a number of media in delivering da'wah messages is either done by using printed or electronic media, therefore in this study, it is stated that the role of mass media is like that of da'i. This research discusses television as a medium of preaching. Television as a media of preaching has advantages and disadvantages, among the advantages of television as a medium of preaching is that television has a very wide reach, it can even reach mad'u who are very far and difficult to reach, television is an amalgamation of audio (voice) media and visual (image). The content of television media can be in the form of information, entertainment or education, it can even be a combination of the three elements. The shortcomings of television as a medium of preaching or as a preacher include the cost of producing television shows which tend to be expensive, because broadcasts on television tend to be profit oriented, so that Islamic programs find it difficult to compete with other programs that are in great demand, such as programs. entertainment, soap operas, films and others.